THE INFLUENCE OF LEADER’S EMOTIONAL INTELLIGENCE ON JOB PERFORMANCE AND WORK ENGAGEMENT AND PSYCHOLOGICAL CAPITAL AS AN INTERVENING IN GRESIK DISTRICT GOVERNMENT - Aminatus Sholikah; Akhmad Fauzi; Arief Bachtiar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study investigates the influence of a leader's emotional intelligence (EI) on job performance and work engagement, with psychological capital as an intervening variable. The research is conducted within the Gresik District Government, focusing on the role of emotional intelligence in improving employee performance and engagement. Using a quantitative approach, the study analyzes responses from 91 respondents. Results show that emotional intelligence significantly impacts psychological capital, job performance, and work engagement. Furthermore, psychological capital is found to mediate the relationship between emotional intelligence and both job performance and work engagement. These findings suggest that enhancing leaders' emotional intelligence can improve organizational performance by fostering a positive work environment and motivating employees.